2020
DOI: 10.1002/mus.26840
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying immobilization‐induced muscle pain in rats

Abstract: Introduction:We investigated the mechanisms underlying immobilization-induced muscle pain in rats. Methods:In rat skeletal muscle, pressure pain threshold (PPT) of the gastrocnemius muscle was measured, and nerve growth factor (NGF) level, peripheral nerve fiber density, macrophage number, and interleukin-1β (IL-1β) mRNA expression were examined. An NGF receptor inhibitor was injected intramuscularly to assess the relationship between PPT and NGF levels.Results: Immobilization resulted in a decrease in PPT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…In a model of immobilizationinduced pain, CGRP-immunoreactive DRG neurons were found to have a larger cell size on the ipsilateral side of immobilization than on the contralateral side, and the intensity of CGRP immunoreactivity was increased in laminae III-IV but not in laminae I-II [13]. The protein levels of NGF, a neurotrophic factor known to cause hyperalgesia and nociceptor sensitization to mechanical and heat stimuli [17], were increased in the skin and muscle of rats after cast immobilization for 4 weeks [18][19][20]. Cast immobilization decreases the thickness of the epidermis and increases NGF expression and the density of nerve fibers immunoreactive for P2X 3 and TRPV1, which are known to be expressed predominantly in small nerve fibers such as unmyelinated C-fibers [6,20].…”
Section: Open Accessmentioning
confidence: 98%
See 1 more Smart Citation
“…In a model of immobilizationinduced pain, CGRP-immunoreactive DRG neurons were found to have a larger cell size on the ipsilateral side of immobilization than on the contralateral side, and the intensity of CGRP immunoreactivity was increased in laminae III-IV but not in laminae I-II [13]. The protein levels of NGF, a neurotrophic factor known to cause hyperalgesia and nociceptor sensitization to mechanical and heat stimuli [17], were increased in the skin and muscle of rats after cast immobilization for 4 weeks [18][19][20]. Cast immobilization decreases the thickness of the epidermis and increases NGF expression and the density of nerve fibers immunoreactive for P2X 3 and TRPV1, which are known to be expressed predominantly in small nerve fibers such as unmyelinated C-fibers [6,20].…”
Section: Open Accessmentioning
confidence: 98%
“…Concerning the heat responses, we detected no changes between the two groups, whereas behavioral nociceptive hypersensitivity to heat was obvious in the immobilization-induced pain model. Recent studies have reported that the expression of NGF proteins is upregulated in the plantar (glabrous) skin and in the gastrocnemius muscle of rats that have undergone hindlimb cast immobilization for 4 weeks [18,19]. NGF is known to induce potent sensitization of nociceptors to mechanical and heat stimuli, resulting in mechanical and heat hyperalgesia [17].…”
Section: Peripheral Mechanisms Of Immobilization-induced Painmentioning
confidence: 99%
“…Macrophages were divided into M1 macrophages (inflammatory macrophages) and M2 macrophages (anti-inflammatory macrophages), M1 macrophages played a key role of fibrous lesion via IL-1β/TGF-β1 signaling. In our previous study, M1 macrophages increased in 2-week immobilized rat skeletal muscles [ 28 ], we surmised that macrophages accumulation was occurred by M1 macrophages increase in immobilized rat soleus muscles. Also, other previous report showed that physical exercise reduced the M1 macrophage response in myocardial ischemic injury [ 29 ].…”
Section: Discussionmentioning
confidence: 85%
“…Multiple receptors have frequently been associated with the development of musculoskeletal pain. Some of the receptors that have been traditionally associated with increased pain include the NGF receptor TrkA ( Hayashi et al, 2011 ; Queme et al, 2013 ; Oga et al, 2020 ) as well as the ion channel TRPV1. Contrary to our expectations, neither of these receptors showed increased expression after the administration of PEGPH20.…”
Section: Discussionmentioning
confidence: 99%